The effect of country image and an institution’s reputation on students’ decision on where to study / Shaiful Azlan Abdul - Shaiful Azlan, Abdul (2014)

(untitled)
The study shows that in Malaysia a country’s image and a university’s reputation are critical factors in influencing students’ selection of a place for study. For Muslim students, the sub-dimension variable of ease of practicing religion is also a significant consideration. The study also shows that perceived quality becomes full and partial mediators for both variables. The fit model for all variables is shown with samples taken nationwide. The data used 1,852 university students from Malaysian universities including 114 international students from four zones of Peninsular Malaysia, namely the northern region covering Perlis, Kedah, Penang and Perak, the Klang Valley region, the eastern region covering Pahang, Terengganu and Kelantan and the southern region covering Negeri Sembilan, Malacca, and Johore. Through questionnaires all 155 items have been created and selected. The evidence is also further supported by four group interviews. The analysis was conducted using structural equation modeling (SEM) and focus group interviews. In the qualitative part of the questionnaire, in terms of majority, the effect of country image outperforms the effect of university reputation in the decision-making by students of various Malaysian universities in their selection of which destination they want to go to. In addition, what is more interesting, when comparisons were made between country, education system, university reputation and personal reason as to which factor influenced them to pursue their study in that particular country, country image often outperforms university reputation as the first ranked influence. Ultimately, the findings indicate that both country image and university reputation are important. The study concludes that a country which has advantages in both variables becomes more successful in terms of becoming favored study destinations. The prepared model shows that for service industries, such as a university environment, the reputation of the university is very important. The study confirms that for the country that has a poor image, only the reputation of its universities can attract students. On the other hand, for the country that has a good image, its universities also have an advantage in attracting students. Keywords: Country Image, University Reputation, Perceived Quality, Ease of Practicing Religion